Spectral Properties, Reconstitution and Kinetics of Paracoccous denitrificans Isovaleryl-CoA Dehydrogenase - Karim, Rafid M.; Hashim, Abdulkareem Jasim (Iraqi Journal of Science, 2022)
Isovaleryl CoA dehydrogenase (IVDH) is a flavoprotein that introduce a trans-double bond between C2 and C3 of the isovaleryl CoA substrate, an intermediate in leucine catabolism pathway. Interrogation of the Paracoccus denitrificans Pd1222 genome has identified Pden_3633 gene as a candidate to encode for IVDH. In previous study by Rafid et al (under the publishing), this putative IVDH was expressed in E. coli and purified as N-terminal Strep-tagged protein. In current study, spectral properties of the purified IVDH were conducted and the results showed that the enzyme was obtained as an apoprotein. For this reason, IVDH has been reconstituted by incubation with flavin adenine dinucleotide (FAD) and the experiment showed that the ratio 1: 20% (IVDH: FAD molar excess) was achieved fully reconstitution. Furthermore, kinetic parameters of the reconstituted IVDH were studied and the enzyme exhibited a specific activity for isovaleryl-CoA substrate while Vmax and KM were estimated to be 600 mU mg-1 and 7.13 μM respectively. Finally, gel filtration by using HiLoad 16/60 Superdex 200 column was performed to investigate the quaternary structure of the recombinant IVDH. An apparent molecular weight of 171640 Da was determined.